2004
DOI: 10.1126/science.1106182
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Competition and Altered Feeding Behavior Among Marine Snails After a Mass Extinction

Abstract: Extinction may alter competitive interactions among surviving species, affecting their subsequent recovery and evolution, but these processes remain poorly understood. Analysis of predation traces produced by shell-drilling muricid snails on bivalve prey reveals that species interactions were substantially different before and after a Plio-Pleistocene mass extinction in the western Atlantic. Muricids edge- and wall-drilled their prey in the Pliocene, but Pleistocene and Recent snails attacked prey only through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 18 publications
0
56
0
Order By: Relevance
“…Drilling on the central part of the valve over adductor muscle scars, described for R. venosa in Chesapeake Bay (Harding et al, 2007), was not observed in our study. Rapa whelks in the Black Sea demonstrated the edge-drilling behavior, which is more risky and may be selectively advantageous in environments where enemies are abundant, especially competitors that might attempt to steal prey (Dietl et al, 2004). Indeed, the bottom communities of the Black Sea are overpopulated by rapa whelks and suffer from high predatory pressure and euthrophication; therefore the competition for prey must be strong.…”
Section: Tablementioning
confidence: 98%
“…Drilling on the central part of the valve over adductor muscle scars, described for R. venosa in Chesapeake Bay (Harding et al, 2007), was not observed in our study. Rapa whelks in the Black Sea demonstrated the edge-drilling behavior, which is more risky and may be selectively advantageous in environments where enemies are abundant, especially competitors that might attempt to steal prey (Dietl et al, 2004). Indeed, the bottom communities of the Black Sea are overpopulated by rapa whelks and suffer from high predatory pressure and euthrophication; therefore the competition for prey must be strong.…”
Section: Tablementioning
confidence: 98%
“…However, the strength of concentric ornament varies greatly among bivalves and the effectiveness of drill holes on ribs is largely unknown. Thus, it is premature to suggest that concentric ornament fails to serve as a protection against drilling predators such as muricid and naticid gastropods, which are important predators of bivalves in modern and ancient oceans (e.g., Kabat 1990;Kowalewski 1993;Kelley and Hansen 2003;Dietl et al 2004;Klompmaker 2009;Sawyer and Zuschin 2010;Chattopadhyay et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported before that the benefits of collective consumption are limited for another muricid Stramonita haemastoma (Brown & Alexander, 1994) and again for a muricid Nucella lapillus Hughes and Dunkin (1984) pointed out the competitive effects of another predator and observed that the other predators or "interlopers" lengthen the pre-consumption inspection and handling times. Another approach, Dietl, Herbert and Vermeij (2004) and Dietl and Herbert (2005) argued that competition may cause changes in the attack type of the predatory snails. Güler and Lök (2016) pointed out dislocation of the snail on its prey due to group-attacking which can cause unsuccessful predation attempts.…”
Section: Discussionmentioning
confidence: 99%